The Tradition of Islamic Philanthropy in Indonesia: Harmony Between Faith and Social Culture - Hidayat, Faisal; Dedat Dingkoroci Akasumbawa, Muhammad; Sahroni, Abdullah (MD Research Center Yogyakarta, 2025)
This study aims to explore the role of Islamic philanthropy, particularly zakat, infak, and waqf, within the social and cultural context of Indonesia. Using a literature review approach, the study examines various previous studies on Islamic philanthropy and its interaction with local wisdom and the practice of gotong royong (mutual cooperation) in Indonesia. The main findings of this study show that Islamic philanthropy not only serves as a religious obligation but also as an essential instrument in strengthening social solidarity and reducing economic inequality in society. Zakat, infak, and waqf have become integral parts of social life in Indonesia, contributing to the improvement of welfare and social justice. The study also reveals how the tradition of Islamic philanthropy can harmonize with Indonesian cultural values, which emphasize the importance of cooperation, mutual assistance, and solidarity. Additionally, the study highlights the critical role of technology in facilitating the management and distribution of philanthropic funds more efficiently and transparently, which is increasingly relevant in today’s digital era. By utilizing a literature review approach, this study provides deeper insights into the vast potential of Islamic philanthropy in supporting socio-economic development in Indonesia, as well as the challenges and opportunities to optimize its impact.